3k-5-10k=23-1k

Simple and best practice solution for 3k-5-10k=23-1k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3k-5-10k=23-1k equation:


Simplifying
3k + -5 + -10k = 23 + -1k

Reorder the terms:
-5 + 3k + -10k = 23 + -1k

Combine like terms: 3k + -10k = -7k
-5 + -7k = 23 + -1k

Solving
-5 + -7k = 23 + -1k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add 'k' to each side of the equation.
-5 + -7k + k = 23 + -1k + k

Combine like terms: -7k + k = -6k
-5 + -6k = 23 + -1k + k

Combine like terms: -1k + k = 0
-5 + -6k = 23 + 0
-5 + -6k = 23

Add '5' to each side of the equation.
-5 + 5 + -6k = 23 + 5

Combine like terms: -5 + 5 = 0
0 + -6k = 23 + 5
-6k = 23 + 5

Combine like terms: 23 + 5 = 28
-6k = 28

Divide each side by '-6'.
k = -4.666666667

Simplifying
k = -4.666666667

See similar equations:

| -2x-2=-6-2 | | 5+2(4x-3)= | | 3x(x+4)-4=2(x+4)+x | | 19.03-12.9h=-14h | | 4x-7-3+2x=8 | | -(3y-6)+4(5y-8)=8 | | -13y+7+9=-10y-11 | | 9(x+3)-5x-3(5+3x)= | | 0.5n-18=-4 | | -q+17=-2q | | 17c-9=18c-19 | | c/8=41 | | -7+3=-5b+17 | | 2(3x-5x)=4x+12 | | 12n+15=11n | | -16+9-15g=1-11g | | -10+9m+3=m+9 | | 6p=15+7p | | r+3/5=4 | | -3w-8=-9w+10 | | -10-2q=-2-3q | | 10h=-8+2h | | 4+8u=-10+10u | | 6x-27=3 | | 3x-12y=-36 | | -2d+2d+8=-4+2d | | Nsquared-10n+22=-2 | | 5t-5=7+8t | | X^2+5-4x=0 | | 52=f-18 | | 24.4=12.4 | | -3(3x-2)=2x+3 |

Equations solver categories